THE POSITION OF DEFENSE COUNSEL IN THE EXTRADITION PROCEDURE IN THE REPUBLIC OF SERBIA: LEGAL FRAMEWORKS OF EXTRADITION AND ENGAGEMENT OF DEFENSE COUNSEL IN EXTRADITION PROCEDURE - Alibašić, Mirsen (Glasnik Advokatske komore Vojvodine, 2023)
The extradition of a defendant or a convicted person is a procedure regulated by law, which enables the conduct of criminal proceedings and the execution of criminal sanctions against said persons in another country. Given that the law regulates the procedure of extradition of the accused or convicted person, the question arises of the position of the defense attorney in that procedure. By applying the normative method in this paper, through the analysis of legal provisions and provisions of international treaties, the position of the defender in the extradition procedure in the Republic of Serbia is systematically presented, i.e. his rights, obligations and permissions in each phase of that procedure with a critical review of individual legal solutions. International standards related to the role and activities of the Committee against Torture and the European Court of Human Rights in relation to the regulation and implementation of the extradition procedure and the position of the defense attorney in that procedure were also presented.
Keywords: defense counsel, lawyer, extradition, hand over, criminal proceedings